CAPITAL STRUCTURE ANALSIS OF INDIAN STEEL COMPANIES: A Vis a Vis Study - RAHUL SHARMA (International journal of economic perspectives, 2022)
This paper is an attempt to study the capital structure of Indian Steel Industry and its determinants. The 66 sample steel companies are bearing an average debt portion of 68% in their capital structure means highly debt driven. Hence we tried to figure out which are the factors significantly explaining the capital structure. For which we have considered eight independent variables from early studies and employed correlation analysis, multiple regression and stepwise regression techniques in this study to test the dependency of the debt ratio on independent variables. We found only three variables such as profitability, growth and risk having significant impact on the debt ratio of these steel companies and following the trend of trade off theory.